China's Arctic ambitions and what they mean for Canada - P. Whitney Lackenbauer; Adam Lajeunesse; James Manicom; Frédéric Lasserre (University of Calgary Press, 2018)
Canada is the one of the first in-depth studies of China's increasing interest in the Arctic. It offers a holistic approach to understanding Chinese motivations and the potential impacts of greater Chinese presence in the circumpolar region, exploring resource development, shipping, scientific research, governance, and security. Drawing on extensive research in Chinese government documentation, business and media reports, and current academic literature, this timely volume eschews the common assumption that China poses an acute threat to Arctic states' polar interests. Instead, it offers a nuanced assessment of how different Chinese stakeholders approach the region and how carefully managed relationships can contribute to positive circumpolar development. Analyzing Chinese interests and activities from a Canadian perspective, the book provides an unparalleled point of reference to discuss the implications for the Canadian and broader circumpolar North.
Keywords: 330; Internationale Beziehungen; Internationale Wirtschaft; Rohstoffpolitik; Außenwirtschaftspolitik; Transitverkehr; Frachtschifffahrt; Kanada; China